The future of population registers: linking routine health datasets to assess a population's current glycaemic status for quality improvement. Issue 4 (28th April 2014) - Chan, Wing Cheuk; Jackson, Gary; Wright, Craig Shawe; Orr-Walker, Brandon; Drury, Paul L; Boswell, D Ross; Lee, Mildred Ai Wei; Papa, Dean; Jackson, Rod
Abstract : Objectives: To determine the diabetes screening levels and known glycaemic status of all individuals by age, gender and ethnicity within a defined geographic location in a timely and consistent way to potentially facilitate systematic disease prevention and management. Design: Retrospective observational study. Setting: Auckland region of New Zealand. Participants: 1 475 347 people who had utilised publicly funded health service in New Zealand and domicile in the Auckland region of New Zealand in 2010. The health service utilisation population was individually linked to a comprehensive regional laboratory repository dating back to 2004. Outcome measures: The two outcomes measures were glycaemia-related blood testing coverage (glycated haemoglobin (HbA1c), fasting and random glucose and glucose tolerance tests), and the proportions and number of people with known dysglycaemia in 2010 using modified American Diabetes Association (ADA) and WHO criteria. Results: Within the health service utilisation population, 792 560 people had had at least one glucose or HbA1c blood test in the previous 5.5 years. Overall, 81% of males (n=198 086) and 87% of females (n=128 982) in the recommended age groups for diabetes screening had a blood test to assess their glycaemic status. The estimated age-standardised prevalence of dysglycaemia was highest in people of Pacific Island ethnicity at 11.4% (95% CI 11.2% to 11.5%) for males and 11.6% (11.4% to 11.8%) for females, followed closely by people of Indian ethnicity at 10.8% (10.6% to 11.1%) and 9.3% (9.1% to 9.6%), respectively. Among the indigenous Maori population, the prevalence was 8.2% (7.9% to 8.4%) and 7% (6.8% to 7.2%), while for 'Others' (mainly Europeans) it was 3% (3% to 3.1%) and 2.2% (2.1% to 2.2%), respectively. Conclusions: We have demonstrated that the data linkage between a laboratory repository and national administrative datasets has the potential to provide a systematic and consistent individual level clinical information that is relevant to medical auditing for a large geographically defined population.